Quantum sensing protocol for motionally chiral Rydberg atoms. (27th August 2021) - Buhmann, S Y; Giesen, S M; Diekmann, M; Berger, R; Aull, S; Zahariev, P; Debatin, M; Singer, K
Abstract: A quantum sensing protocol is proposed for demonstrating the motion-induced chirality of circularly polarised Rydberg atoms. To this end, a cloud of Rydberg atoms is dressed by a bichromatic light field. This allows to exploit the long-lived ground states for implementing a Ramsey interferometer in conjunction with a spin echo pulse sequence for refocussing achiral interactions. Optimal parameters for the dressing lasers are identified. Combining a circularly polarised dipole transition in the Rydberg atom with atomic centre-of-mass motion, the system becomes chiral. The resulting discriminatory chiral energy shifts induced by a chiral mirror are estimated using a macroscopic quantum electrodynamics approach. The presented quantum sensing protocol will also provide an indirect proof for Casimir–Polder quantum friction.